The "Temukan, Obati Sampai Sembuh" (TOSS) Movement in Breaking Pulmonary Tuberculosis Transmission at Bambaira Health Center, Pasangkayu - Nur Afni; Muhammad Jufri; Sudirman; Ahmad Yani; Muhammad Syukran; Indra Afrianto (Public Health of Indonesia, 2025)
Background: Tuberculosis (TB) remains a global health challenge. Indonesia ranks among countries with the highest TB burden, with over 800,000 cases reported in recent years (WHO, 2024). The Ministry of Health introduced the Temukan, Obati, Sampai Sembuh (TOSS) initiative to enhance early detection and treatment adherence. However, implementation barriers persist, especially in remote areas. Objective: This study aims to evaluate the implementation of the TOSS TB program in breaking TB transmission at Bambaira Health Center, Pasangkayu Regency, and to identify systemic challenges and improvement opportunities. Methods: This qualitative study used in-depth interviews, FGDs, observations, and document analysis. Participants included healthcare workers, TB patients, caregivers, and community leaders. Thematic analysis was conducted to explore program implementation. Results: Barriers identified include poor public awareness, weak contact tracing, medication stockouts, and limited follow-up systems. Stigma also discouraged patients from seeking care. Nevertheless, early case detection and initial treatment showed promising outcomes when supported by trained staff and community involvement. Conclusion: Addressing systemic barriers through education, logistics, and community engagement is key to TOSS TB success. Policy support and consistent funding are needed to ensure sustainability and integration with other health services. Keywords: tuberculosis; TOSS TB;  health center; public health; Indonesia